THE APPLICATION OF PROBLEM BASED LEARNING (PBL) MODEL TO IMPROVE THE LEARNING OUTCOMES OF HISTORY CLASS X SMK PGRI AIR BELITI - Prastika, Anis; Susilo, Agus; Isbadiyah, Isbadiyah (JURNAL EDUSCIENCE, 2024)
This research aims to determine the completensess of the learning outcomes of class X students at SMK PGRI Air Beliti after using the Problem Based Learning (PBL) model. The method used is a quantitative method with a pseudo-experimental research desing. The population in this study were clas X students consisting of two classes. The sampling technique used was random sampling technique, where the sample was chsen randomly after being given a lottery number and shaken which become the research sample for clas X.B of  28 Students. The data collection technique used was pre-test  and post-test using a test in the form of multiple choice questions. Tne analisys requirements testing technique uses a one sample z-test. The results of this study showed the average pre-test scor was 51,71 with a completeness percentage of completeness 0% or none of the students were complete, while the average post-test score was 74,89 with a completion percentage of 78,57% or 22 students completed. The z-table results obtained calculated Z value 3,11) ≥ Z table (2,052). The conclusion is that the application of problem based learning model on the history learning outcommes of class X SMK PGRI Air Beliti is significantly complete.